(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Information Technology (IT) plays a critical role in delivering education services to users. To assist students, professors, researchers, and administrative personnel, most education online services at universities have been run on the cloud. These are made possible by the rise of cloud computing in the IT industry. Cloud computing provides Internet-based computer services on demand. The use of cloud computing in higher education, namely tertiary institutions and universities, is discussed in this article. The difficulties of cloud computing in higher education are the subject of the article. It examines studies on adoption difficulties in higher education institutions and provides background on cloud computing. These difficulties are significant because they offer an overview of cloud adoption in higher education. To study the variables that affect users’ attitudes and behaviors about utilizing The authors established an integrative references framework based on difficulties in the research and the TAM model for cloud educational solutions in schools’ ICT offering.